Morphological Integration of English-Origin Loanwords in Inuktitut (LITPAM, 2025)
English-origin loanwords in Inuktitut are integrated morphologically. As an example, the Inuktitut word guulu, from English “gold”, can undergo affixation with the bound morphemes siuq, meaning “to search for”, and vik, denoting a place where an action takes place, to create the word guulusiurvik, meaning “gold mine”, then attach to grammatical markers that indicate the function of the new word within the sentence. This paper investigates how and why these loanwords are morphologically integrated, as well as the variation observed in this integration. The corpus used for this investigation was The Nunavut Hansard Inuktitut-English Parallel Corpus 2.0, containing transcripts of all the proceedings of the Legislative Assembly of Nunavut from April 1999 to November 2007, excluding 2003. Within the corpus, the following selection of English-origin loanwords was assessed: paper, company, license, cigarette, tobacco, cheque, skidoo, gold, bus, and coffee. It is suggested that an established morphological framework for integrating loanwords in Inuktitut stems out of necessity due to the typological differences between Inuktitut and English, however individual deviations arise from liberties taken by bilingual speakers in their speech when drawing on both Inuktitut and English grammatical and morphological systems while using an English-origin loanword. These findings are relevant to the linguistic documentation of Inuktitut and shed light on the language contact situation between the Indigenous language Inuktitut and the settler language English.